Endovascular management of splenic artery aneurysms in women of childbearing age: a case report and a review of literature - Kanbar, Karim; Muallem, Nadim; Hoballah, Jamal J. (Frontiers in Surgery, 2025)
IntroductionSplenic artery aneurysms (SAAs), though rare, are the most common splanchnic artery aneurysms and carry high maternal and fetal mortality if ruptured during pregnancy. Despite growing awareness, optimal long-term management and follow-up in women of childbearing age remain unclear.Presentation of caseWe report a case of a healthy 37-year-old gravida 2 para 2 woman with an incidentally discovered 1.4 cm mid-splenic artery aneurysm on follow-up imaging after gastric banding. Due to her reproductive potential, endovascular treatment was performed. Coil embolization of two small branches arising from the aneurysm sac was followed by placement of a balloon-mounted 7 mm covered stent across the aneurysm neck. The procedure was uncomplicated, and post-intervention imaging confirmed aneurysm exclusion and preserved distal flow. Follow-up at 3 and 6 months showed complete thrombosis of the sac, patent stent, and no evidence of infarction. Ten months later, the patient had an uneventful pregnancy and delivery.DiscussionEndovascular approaches are increasingly preferred over surgery due to lower morbidity and better fertility preservation. Coiling is effective but may risk recanalization or infarction. Covered stents offer structural stability, preserve splenic flow, and allow clearer imaging follow-up. However, challenges include delivery in tortuous vessels and a potential endoleak. In our case, combining coiling of branches with stenting ensured aneurysm exclusion while supporting safe pregnancy.ConclusionStent grafting with selective coiling is a safe and effective option for managing SAAs in women of childbearing age. This case demonstrates successful treatment with long-term follow-up through pregnancy, though further research is needed to establish definitive guidelines.